Road traffic risk, civil liability and autonomous vehicles (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Artificial Intelligence is a general-purpose technology capable of generating as many revolutions as its potential fields of application. Among these revolutions, the one related to autonomous vehicles stands out, as it is capable of changing the way of understanding the very concept of mobility. This essay aims at analyzing the relationship between autonomous vehicles and civil liability seen through the change in the perception and measurement of the risk related to road traffic as a factor capable of affecting the traditional functions performed by motor vehicle liability rules.
Keywords: Artificial Intelligence; autonomous vehicles; road traffic risk; civil liability; product mobility